Pengembangan E-media Pembelajaran Interaktif pada Mata Pelajaran Dasar Listrik dan Elektronika - Zul Vandri; Usmeldi Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
This research was conducted because of the limited use of instructional media that can guide students to understand learning material easily because the teacher focuses students on understanding concepts that tend to be passive. The use of less varied media has an impact on students' interest in learning. This interactive learning media was developed in order to promote more interesting learning, increase understanding, strengthen memory, and learning media are expected to foster student interest in learning. This study aims to produce interactive e-learning media that are valid, practical, and effective. This study uses a research and development method (Research and Development) with a 4-D model consisting of 4 stages, namely the define, design, develop, and disseminate stages. This research was conducted on class X TITL students at SMK N 1 Pariaman. The results in this study are interactive e-media learning, including the valid category. The practicality of interactive e-learning media is very practical. The effectiveness of interactive e-learning media is in the effective category. Based on the research results obtained, it is concluded that the developed interactive learning media is valid, practical, and effective.